An Influence Of Quality Management System For Improvement Of Logistics Supply - Dominik Zimon (Institute of Economic Research (IER), 2017)
Research background: ISO 9001 with its requirements gives a company a guidance on the definition of the quality management system architecture, based on the process approach and the indications for its continuous improvement. Despite the general accentuation the benefits of implementation of ISO 9001 in the literature, there is still lacks of researches concerning the actual impact of quality management systems for improving specific logistics processes (especially in Polish organizations). Purpose of the article: The aim of this publication was to examine the impact of the implementation of the requirements of ISO 9001 for process improvement supply logistics. Methodology/methods: Empirical studies were carried out in September and October 2014 on a group of 17 companies with implemented and certified quality management system according to ISO 9001. The research tool was a questionnaire survey sent to management representatives (25 respondents) and workers (140 respondents). Surveys were enriched with direct interviews with employees of the companies. The impact of the quality management system for the improvement of procurement processes - presentation and analysis of the test results. Findings: Based on the survey it can be stated that the quality management system according to ISO 9001 in a fairly large impact on improving procurement processes. This is particularly evident in areas including relationships with suppliers, quality control, workflow and communication, both internal and external. The positive aspects achieved through the implementation of quality management system due to the fact that the ISO 9001 standard in its commitments puts great emphasis on the organization of the procurement process. Good in that supplies the organization must meet specified purchase requirements including approval processes semi-finished products, qualifications and functioning of the quality management system provider.
Keywords: D2; D21; 330; ISO 9001; logistics supply; quality; systems